2023
DOI: 10.19040/ecocycles.v9i1.263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of highway design on traffic safety: How geometric elements affect accident risk

Abstract: The study conducted in India using Fuzzy Inference System (FIS) is a novel approach to predicting traffic accident rates on rural highways. By using various highway geometric elements as input data, the study was able to identify risk variables related to roadway features and predict accident rates using FIS. The findings of the study suggest that FIS is a valuable tool for predicting accident rates and can help identify the factors that contribute to accidents. The study also found statistically significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Garnaik [64] studied 70 km of roads and found that geometric elements of road alignment, such as superelevation, radius, K-value, distance/visibility of sight and vertical gradient, are very significant in causing accidents on both plain and rolling roads as well as mountainous and steep terrain. Meanwhile, the horizontal arc length, deflection angle, vertical curve length, and rate of change of superelevation are insignificant to accidents on both the highway and mountainous and steep terrain.…”
Section: Road Geometric and Road Safetymentioning
confidence: 99%
“…Garnaik [64] studied 70 km of roads and found that geometric elements of road alignment, such as superelevation, radius, K-value, distance/visibility of sight and vertical gradient, are very significant in causing accidents on both plain and rolling roads as well as mountainous and steep terrain. Meanwhile, the horizontal arc length, deflection angle, vertical curve length, and rate of change of superelevation are insignificant to accidents on both the highway and mountainous and steep terrain.…”
Section: Road Geometric and Road Safetymentioning
confidence: 99%
“…3D alignment models provide a more comprehensive understanding of the driving experience. Tey enable designers to visualize clear-sight triangles, simulate curves and grades, identify concealed dangers, and analyze collisions from multiple angles [26]. Studies have demonstrated that 3D alignment design signifcantly improves safety over 2D methods [23].…”
Section: Literature Reviewmentioning
confidence: 99%